Pengembangan Teknologi ERP untuk Modul HRM Studi Kasus PT Indonesia Prima Equipment (Mitra JCB) - Muhammad Adam Suryana; Slamet Riyadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
PT. Indonesia Prima Equipment (Mitra JCB) is a company under the auspices of the Mitra Cakrawala International Group (MCI Group), a company engaged in the distribution of heavy equipment under the JCB Brand. However, the company in managing employees starting from employee recruitment, providing employee training, updated employee data, attendance, appraisal, remuneration, submission of transfer, training and promotion is still not fully computerized so that sometimes the company is difficult to find and process data relating to human resources in the company. ERP is a system consisting of software packages with integrated applications for wide use within the company. Meanwhile, Human Resource Management is an important module in ERP that provides support for all functional information systems of the company. Human Resource Management is needed to increase the effectiveness of human resources in the company. The aim is to provide the company with an effective work unit. To achieve this goal, Human Resources Management will show how the company should get, develop, use, evaluate, and maintain employees in the right number and type.